'But I don't want to lead a group!' Some common problems of social workers leading groups - Reid, Ken (Groupwork, 2020)
There is a general fear by both social work students and practitioners of leading groups. One result is that a majority of social workers do dyadic or family counselling and avoid groupwork in their practice. The article deals with fears and fantasies, linked to a perceived loss of power and control, experienced by the social worker leading groups. It also addresses some of the common problems workers face in creating and maintaining groups, including lack of authenticity, misuse of techniques, ignoring process and reluctance to confront, and suggests practical ways the problems cm be addressed. Publisher’s note: We are now putting all back issues of Groupwork on line. Articles in this issue have been scanned to pdf files as viable original typesetting files no longer exist. Though they may not look it, these files are searchable. This issue was published nearly 30 years ago. We have stated author professional details as received at time of publication. Abstracts are word-for-word transcriptions of the original abstracts with no attempt to update terminology.